A Comparative Study on Accuracy and Reproducibility of Alginate and Addition Reaction Silicone as an Impression Materials. - Fatema, Shakila; Quader, Sheikh Md Shahriar; Shamsuzzaman, Mohammad; Rahman, Mirza Md Arifur; Khan, Nasima (Update Dental College Journal, 2014)
Background: To achieve accuracy and exact reproduction of prosthesis, choosing a perfect impression material is essential. Especially to make the prosthesis as accurately as possible, impression material should possess some essential properties, like; minimum dimensional changes, good flow ability and easy removal. Purpose: The aim of this study was to evaluate the accuracy and surface detail reproduction of Alginate and Addition Reaction Silicone as an impression materials. Method: This is an experimental in vitro study. In this study Impression by Alginate and Addition Reaction Silicone were made using a round stainless steel test block with three horizontal lines and two vertical lines. The horizontal lines were used for evaluating the surface detail reproduction, and vertical lines were provided for the dimensional accuracy. For dimensional accuracy the length of the middle horizontal line in between vertical lines and the distance between the top and bottom horizontal line was measured using travelling microscope. And for surface detail reproduction three horizontal line of one segment were observed under stereomicroscope. Result: According to study results Addition Reaction Silicone is better than Alginate regarding quality of impression. Conclusion: In comparison to Alginate, Addition Reaction Silicone might have better performance about accuracy and surface detail reproduction. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17996 Update Dent. Coll. j: 2013; 3 (2): 28-33